Potential action of extract of Acmella oleracea (L.) R.K. Jansen to control Amblyomma cajennense (Fabricius, 1787) (Acari: Ixodidae) ticks - Anholeto, Luís Adriano [UNESP]; Oliveira, Patrícia Rosa de [UNESP]; Rodrigues, Rodney Alexandre Ferreira; Spindola, Caroline dos Santos; Labruna, Marcelo Bahia; Pizano, Marcos Aparecido [UNESP]; Castro, Karina Neoob de Carvaldo; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier, 2017)
The use of synthetic acaricides is currently the main method to control ticks. However, the indiscriminate use of these chemicals can lead to the selection of resistant individuals and in the accumulation of chemical residues in the environment, contaminating the soil and water streams, consequently affecting the flora, fauna, and the human beings as well. In this sense, the objective of this study was to investigate the acaricidal effect of crude ethanolic extract of Acmella oleracea (L.) R.K. Jansen aerials parts at different concentrations on fed males and semi-engorged females of A. cajennense s.s. An in vitro bioassay (Adult Immersion Test) was carried out to determine the lethal concentration 50 (LC50) of ethanolic extract, calculated by Probit analysis. The results showed that the fed males were sensitive to all the concentrations of A. oleracea ethanolic extract, and mortality rate progressively increased (15–65%) in higher ethanolic extract concentrations. However, semi-engorged females were not sensitive to all the concentrations used here. In the highest concentration (100 mg/mL), a mortality rate of 100% was observed after 72 h of exposure, indicating that the acaricidal effect would probably be dose-dependent. The LC50 values obtained for the fed A. cajennense s.s males and semi-engorged females were 29.4534 mg/mL (limits: 24.4467–41.3847 mg/mL) and LC50 = 17.6335 mg/mL (limits: 5.2506–23.5335 mg/mL), respectively.
Keywords: Acaricide; Jambu; LC50; Natural control; Ticks